2021
DOI: 10.1002/iid3.522
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of obesity on COVID‐19 patients discharged from hospital

Abstract: Introduction: Obesity has been reported as a risk factor for COVID-19 prognosis. However, the long-term effects of obesity on patients discharged from the hospital are unclear, and the present study aims to address this issue.Methods: A cohort study was conducted using data from patients diagnosed with COVID-19 who were discharged from Wuhan Union Hospital between February 20, 2020, and March 20, 2020. The 118 patients with COVID-19 were divided into the non-obesity group and the obesity group according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Finally, we reviewed the full text of 15 articles and included 15 observational studies (11 from China, three from Italy and one from the United Kingdom, N = 3134). Egger's test did not suggest a significant publication bias ( p = 0.994) (Figure 1 and Figures S1 and S2 in the Supporting Information) 6,8–21 …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Finally, we reviewed the full text of 15 articles and included 15 observational studies (11 from China, three from Italy and one from the United Kingdom, N = 3134). Egger's test did not suggest a significant publication bias ( p = 0.994) (Figure 1 and Figures S1 and S2 in the Supporting Information) 6,8–21 …”
Section: Resultsmentioning
confidence: 96%
“…Between the mid‐term and 1‐year follow‐up, 138 patients were lost to follow‐up; therefore, 1801 patients were evaluated for CT at 1 year (Figure S3 and Table S2 in the Supporting Information). Three studies did not report the proportion of overall residual CT abnormalities but reported other specific findings 12,16,21 . The proportion of patients with any residual CT abnormalities in 12 studies was estimated to be 32.6% (512/1629, 95% CI 24.0–42.6, I 2 = 92.9%; Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 33 Another article suggests that the indexes of liver function in obese patients were significantly abnormal, and that the antibody titer of COVID-19 in obese patients was negatively correlated with BMI. 34 Our research shows that GGT is a risk factor for stage T3 liver function abnormality. Studies have shown that GGT is associated with the severity of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 59%